Molecular Identification of Microbes from the Soil Rhizosphere of Cocoa as A Potential Biofertilizer - Nurmayulis Nurmayulis; Abdul Hasyim Sodiq; Fitria Riany Eris; Dewi Hastuti; Yus Rama Denny; Dwi Ningsih Susilowati (AGRIVITA, Journal of Agricultural Science, 2023)
There are three microbes that originated from the roots (Rhizosphere) of the cocoa plant (Theobroma cacao L.) as a potential biofertilizer. This research aimed to specify the ability of microbial isolates in a consortium with the addition of Biosurfactant Diethanolamide. The three microbes were observed using synergism test, molecular and population identification in the consortium. The synergism test showed the three isolates were not mutually antagonistic indicated there was no clear zone around the colony. The molecular identification showed the isolate 1 was as Bacillus substilis (99.88% hegemony), isolate 2 was as Bacillus substilis (99.75% hegemony) and isolate 3 was as Bacillus amyloliquefaciens (100% hegemony). The population consisted of Â 3.6 x 106 cfu/ml Azotobacter, 0.55 x 101 cfu/ml Azospirillium and 2.5 x 105 cfu/ml phosphate solubilizing bacteria. The results of the calculations on the microbial consortium with the addition of Biosurfactant Diethanolamide were 3.75 x 106 cfu/ml Azotobacter, 0.1 x 102 cfu/ml Azospirillium and 1.65 x 105 cfu/ml phosphate solubilizing bacteria.